Operational control of an average beam energy at a technological electron linac - Boriskin, V.N.; Dovbnya, A.N.; Myakushko, L.K.; Reprintsev, L.V.; Tatanov, V.I.; Shendrik, V.A. (Вопросы атомной науки и техники, 2006)
The paper reports the results of development of a technique for beam uninterrupted measurement, and also some experimental
data from measurements of an average electron beam energy at the technological accelerator KUT-20. The
technique involves a compact pulsed magnet-deflector and a transit-time monitor of beam center position. The magnet is
excited by a meander-type current pulse of 300 ms duration. The equipment used provides measurements up to 40 MeV.
A relative error of measurements makes 5%. Приведены результаты разработки и некоторые экспериментальные данные измерения средней энергии пучка электронов в технологическом ускорителе КУТ-20 без прерывания пучка. Блок измерения включает в себя компактный импульсный магнит–дефлектор и пролетный монитор положения центра пучка. Магнит возбуждается импульсом тока типа «меандр» длительностью 300 мс. Используемая аппаратура позволяет проводить измерения до 40 МэВ. Относительная погрешность измерений составляет 5%. Приведені результати розробки і деякі експериментальні дані вимірювання середньої енергії пучка
електронів в технологічному прискорювачі КУТ-20 без перерв пучка. Блок вимірювання включає в себе
компактний імпульсний магніт–дефлектор і пролітний монітор положення центра пучка. Магніт збуджується
імпульсом струму типу «меандр» тривалістю 300 мс. Використовувана апаратура дозволяє проводити
вимірювання до 40 МеВ. Відносна похибка вимірювання складає 5%.